Intravenous ketamine in gynaecological surgeries reduces pain score and opioid consumption - Huda, Anwar ul; Minhas, Raheel; Yasir, Mohammad (Journal of the Pakistan Medical Association, 2022)
Objective: To assess the effect of intravenous ketamine on postoperative pain control, opioid consumption, and the incidence of postoperative adverse events in gynaecological surgeries. Method: The systematic review and meta-analysis was conducted in July 2020 and the search was repeated in July 2021 to ensure accuracy. The review was registered with the International Prospective Register of Systematic Reviews (PROSPERO) in July 2020. The search, done on online databases Medline and Science Direct, comprised studies on patients who underwent general anaesthesia for gynaecological surgeries and received intravenous ketamine intraoperatively, and the findings included opioid consumption, postoperative pain control, and associated side-effects. Results: Of the 79 randomised controlled trials found, 9(11.4%) were subjected to meta-analysis. The use of intravenous ketamine reduced pain score at 2h (p=0.003) and 24h (p=0.002) postoperatively in gynaecological surgeries. In laparoscopic gynaecological surgeries, lower pain scores were reported at 1h (p=0.01) and 2h (p=0.002) hours postoperatively. Lower pain scores were reported at 24h postoperatively in open gynaecological surgeries (p=0.002). Intravenous ketamine increased the time to first-request analgesia postoperatively (p=0.03), and reduced postoperative 24h opioid consumption (p=0.002). Conclusion: The use of intravenous ketamine significantly reduced postoperative pain at 2h and 24h after gynaecological surgeries and at 1h and 2h after laparoscopic gynaecological surgeries. Key Words: Ketamine, Pain score, Gynaecological surgery, Opioid consumption.